2019
DOI: 10.1298/ptr.r0006
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous neuroprotective potential due to preconditioning exercise in stroke

Abstract: Stroke is a leading cause of serious long-term physical disability due to insufficient neurorepair mechanisms. In general, physical activity is an important modifiable risk factor, particularly for stroke and cardiovascular diseases. Physical exercise has shown to be neuroprotective in both animal experiments and clinical settings. Exercise can be considered a mild stressor and follows the prototypical preconditioning stimulus. It has beneficial effects on brain health and cognitive function. Preconditioning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Finally, exercise's anti-ischemic effect may be also linked to the mechanism of preconditioning [134]. Preconditioning is defined as the exposure of a system or an organ to a conditioning stimulus to induce tolerance or resistance to a subsequent injury [135] by triggering cells and organisms to express intrinsic protective factors, thus helping them acquire tolerance and self-defense against later possible damage [136].…”
Section: Anti-ischemic Effects Of Physical Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, exercise's anti-ischemic effect may be also linked to the mechanism of preconditioning [134]. Preconditioning is defined as the exposure of a system or an organ to a conditioning stimulus to induce tolerance or resistance to a subsequent injury [135] by triggering cells and organisms to express intrinsic protective factors, thus helping them acquire tolerance and self-defense against later possible damage [136].…”
Section: Anti-ischemic Effects Of Physical Activitymentioning
confidence: 99%
“…Preconditioning is defined as the exposure of a system or an organ to a conditioning stimulus to induce tolerance or resistance to a subsequent injury [135] by triggering cells and organisms to express intrinsic protective factors, thus helping them acquire tolerance and self-defense against later possible damage [136]. Several studies have demonstrated that preconditioning exercise (i.e., prophylactic exercise prior to stroke) provides significant neuroprotection against acute stroke through the promotion of angiogenesis, mediation of inflammatory responses, and inhibition of neuronal apoptosis [134]. In the 2,3,5-triphenyltetrazorlium chloride (TTC) study, the tissue infarction in rats with preconditioning exercise was decreased compared with the brain of rats without preconditioning [134].…”
Section: Anti-ischemic Effects Of Physical Activitymentioning
confidence: 99%
See 3 more Smart Citations